Cryopreservation Effect on Differentiation Capacities of Mesenchymal Stromal Progenitor Cells from Human Fetal Liver and Adult Bone Marrow - Skorobogatova, N. G.; Petrenko, Yu. A.; Volkova, N. A.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2013)
The cryopreservation influence on osteogenic and adipogenic capacities of expanded in vitro mesenchymal stromal cells derived from human fetal liver and adult bone marrow was investigated. Saving proliferative ability and differentiation potential of the progenitor cells after cryopreservation by 2-step slow freezing under Me2SO protection was shown.